Algorithms for Solving Systems of Equations and Inequalities with Applications in Nonlinear Programming - Huang, T.J. (University of Wisconsin-Madison Department of Computer Sciences, 1973)
Global algorithms are proposed for solving systems of nonlinear equations and inequalities. Global convergence is established under suitable assumptions. For some special cases, the rate of convergence is R-superlinear. A global algorithm for solving convex programming problems is also given. Computational results for one of the algorithms are given.